Metode Dakyah Kristian di Pulau Pinang Pada Abad ke-19: Kajian Terhadap Karya-Karya Terpilih Thomas Beighton (1790-1844): Methods of Christian Mission in Penang in the 19th Century: A Study of the Selected Works of Thomas Beighton (1790-1844) - Ngadiran, Siti Nor Aisyah; Denisova, Tatiana A. (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
The British settlement in Penang in the 1790s had led to the introduction of Christianity from various sects, mainly Protestant which consisted of multiple missionary societies. Amongst the most active was the London Missionary Society (LMS). However, the research conducted on LMS especially among the local researchers is minimal due to the lack of sources which are only available in certain libraries in London. Therefore, this study aims to introduce 10 works of Thomas Beighton (1790–1844) which were written in Malay Jawi. These sources highlighted the importance of this language as an element of Malay identity in Penang. Hence, textual analysis, classification and comparison methods employed by using ATLAS.ti were done to identify the preaching methods that are often used in these works. The results indicated that there were three main methods; highlighting of the similarities between Islam and Christianity, the misrepresentation of the image of Islam and the Malays, and promoting of Western ethics and Christianity as a solution in life. However, the Beighton’s mission failed when the LMS Malay Missionary Station in the region had to be closed down and consequently, they turned their attention to China in 1843.